Collaboration Model in Blended Learning-Based Training: A Case Study at the Center for State Civil Apparatus Training, Development and Competency Mapping of the National Institute of Public Administration - Ella, Susy; Andari, Rosita Novi; Amalia, Shafiera; Nugroho, Candra Setya (Puslatbang KDOD Lembaga Administrasi Negara, 2024)
This study proposes the collaboration model for implementing blended learning based civil apparatus training programs. This study adopted a mixed-method approach, integrating quantitative and qualitative data into the Delphi process to develop a collaboration model for stakeholders in blended learning-based civil apparatus training. The results reveal a model describing the identification of the actors and their roles and the process and prerequisites in collaborating with the blended learning-based civil apparatus training programs. The study offers valuable insights for training institutions and stakeholders involved in similar initiatives, providing practical guidance derived from recommendations to enhance collaborative training practices, ultimately aiming to improve the effectiveness and efficiency of training programs